Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The Effectiveness of Teachers’ Job Performance Assessment in the Schools of Al-Batinah North Governorate, Sultanate of Oman in Their PerspectiveMr. Mohammed Salim Ali Al-Jahwari2. A comparative study between the Higher Education Council system of 1993 and the universities system of 2019 in the Kingdom of Saudi ArabiaDr. Saud Ghassan Albeshir3. The reality of school crises management in public schools in capital city of sana'a, Republic of YemenMrs. Amal Mahfoud Khaled Abdalwahab4. Prophetic educational methods in addressing some manifestations of bullying among students as recognized by middle school teachersMr. Ahmed Mohammed Al- Essi5. The mediating role of positivity in the relationship between psychological immunity and emotional control among health sector workers in Erbil cityDr. Izaddin Ahmad Aziz, Mrs. Delan Abdullah Mahmood6. Kindergarten teachers' knowledge of the initial indicators of autism spectrum disorderMrs. Frah Ekram Mukhtar, Dr. Salwa Mustafa Khishaim7. The effectiveness of digital stimuli in improving attention among students with mental disabilitiesMr. Osama Musa Althaghafi
Keywords: Journal of Educational and Psychological Sciences